Estructura funcional de la Comisión de Bioética Nacional y las subcomisiones de ética para la investigación Universitaria - Garcés Giraldo, Luis Fernando (Corporación Universitaria Americana, 2018)
The Corporación Universitaria Americana, as an educational institution responsible for its quality processes, has within its substantive functions that of research; in it, the evaluation of the research projects presented for execution is a priority and where it is important to verify their ethical conditions, based on national standards and policies, which should undoubtedly aim for the conditions and welfare of living beings and the commitment to the information obtained from their research; in addition, the verification of the conditions and qualities of the researchers involved in all types of research.